Malignant phaeochromocytoma and hypercalcaemia. - Bridgewater, J. A. (BMJ Group, 1993)
We describe a case of hypercalcaemia secondary to recurrent malignant phaeochromocytoma. Parathyroid-related protein (PTHrp 1-86) immunoreactivity was identified in plasma and PTHrp was identified by immunocytochemistry in tumour tissue.